1978
DOI: 10.1093/ptj/58.12.1467
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neural Excitability: Implications for Transcutaneous Electrical Nerve Stimulation

Abstract: Basic neurophysiological principles necessary for understanding the effectiveness of transcutaneous electrical nerve stimulation are presented. Peripheral and central neural mechanisms are reviewed, and the effects of individual pulse characteristics on neural excitability are analyzed. Representative commercial stimulators are compared, and wave-forms for different load conditions are illustrated. Discussion includes important considerations for clinical effectiveness and for patient acceptance and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
1
19
2
Order By: Relevance
“…Non-invasive alternatives to needle acupuncture have been explored using transcutaneous nerve stimulators with selected treatment parameters, such as the acupuncture-like transcutaneous nerve stimulator (ALTENS). A-delta and C nerve fibres that are involved in needle acupuncture treatment with the typical ‘De qi’ response (experienced as a mild ache by the subject) can be activated by ALTENS using high intensity and low frequency stimulation 20, 21, 22 . The use of electrode pads that are 3 to 4 cm in size also make the precise localization of acupuncture points (usually 0.5 to 2 cm in size) less important.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive alternatives to needle acupuncture have been explored using transcutaneous nerve stimulators with selected treatment parameters, such as the acupuncture-like transcutaneous nerve stimulator (ALTENS). A-delta and C nerve fibres that are involved in needle acupuncture treatment with the typical ‘De qi’ response (experienced as a mild ache by the subject) can be activated by ALTENS using high intensity and low frequency stimulation 20, 21, 22 . The use of electrode pads that are 3 to 4 cm in size also make the precise localization of acupuncture points (usually 0.5 to 2 cm in size) less important.…”
Section: Discussionmentioning
confidence: 99%
“…26) In addition, it is known that the amplitude of electrical current necessary to excite nerve fiber tends to diminish as its pulse duration and frequency increase. Some findings from animal and human studies reported that conventional TENS produces segmental analgesia with a rapid onset and offset which was predominantly localized to the dermatome.…”
Section: Gate Control Theorymentioning
confidence: 99%
“…Strength-duration curves for sensory, motor, and pain tolerance thresholds converge at longer phase durations, i.e. there is less separation between pain and motor thresholds, so the increase in discomfort with phase duration is perhaps not unexpected [41][42][43] .…”
Section: Discomfort and Stimulus Phase Durationmentioning
confidence: 99%